Diffusion with a Discontinuous Potential: A Non-Linear Semigroup Approach (Analysis in Theory and Applications, 2021)
This paper studies existence of mild solution to a sharp cut off model for contact driven tumor growth. Analysis is based on application of the Crandall-Liggett theorem for $ω$-quasi-contractive semigroups on the Banach space $L^1(Ω)$. Furthermore, numerical computations are provided which compare the sharp cut off model with the tumor growth model of Perthame, Quirόs, and Vázquez [13].